2018
DOI: 10.1159/000486450
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Performance of Lowlanders with COPD at 2,590 m: Data from a Randomized Trial

Abstract: Background: Effects of hypobaric hypoxia at altitude on exercise performance of lowlanders with chronic obstructive pulmonary disease (COPD) have not been studied in detail. Objectives: To quantify changes in exercise performance and associated physiologic responses in lowlanders with COPD travelling to moderate altitude. Methods: A total of 31 COPD patients with a median age (quartiles) of 66 years (59; 69) and FEV1 of 56% predicted (49; 69) living below 800 m performed a constant-load bicycle exer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 39 publications
(58 citation statements)
references
References 32 publications
6
49
3
Order By: Relevance
“…The higher PAP in COPD patients is most likely due to both restriction of the pulmonary vascular bed due to parenchymal destruction of the lung and a greater degree of hypoxemia with excessive hypoxic pulmonary vasoconstriction. We did not find any significant increase in breath rate or dynamic hyperinflation with altitude in the present COPD cohort [30], and changes in functional residual capacity and the TPG were not correlated. Thus, we do not think that any changes in respiratory mechanics contributed to the increase in PAP in these patients.…”
Section: Discussioncontrasting
confidence: 88%
“…The higher PAP in COPD patients is most likely due to both restriction of the pulmonary vascular bed due to parenchymal destruction of the lung and a greater degree of hypoxemia with excessive hypoxic pulmonary vasoconstriction. We did not find any significant increase in breath rate or dynamic hyperinflation with altitude in the present COPD cohort [30], and changes in functional residual capacity and the TPG were not correlated. Thus, we do not think that any changes in respiratory mechanics contributed to the increase in PAP in these patients.…”
Section: Discussioncontrasting
confidence: 88%
“…Some physiological outcomes evaluating gas exchange, cerebral blood flow, and cerebral and muscle tissue oxygenation as a part of the current trial have been reported recently. 4 Apart from baseline characteristics of study participants, the data presented here have not been published except previously in abstract form. The study was approved by the Cantonal Ethics Committee of Zurich (EK-2013-0088), subjects gave written informed consent, and the trial is registered at www.ClinicalTrials.gov : NCT01875133.…”
Section: Methodsmentioning
confidence: 99%
“…In a recent physiological investigation, we observed a reduction of submaximal constant load bicycle exercise by about one half due to systemic and cerebral hypoxemia in a group of COPD patients at 2,590 m compared with the performance at their low altitude residence. 4 To provide a scientific basis to counsel COPD patients planning altitude sojourns, the current study evaluated the effect of travel to altitudes of 1,650 and 2,590 m for a total of 4 days on exercise performance, general well-being, and several other outcomes in lowlanders with moderate to severe COPD.…”
Section: Introductionmentioning
confidence: 99%
“…In a previous study in PH patients assessed during short-term exposure to normobaric hypoxia during right heart catheterization (15 min, FiO 2 15%), we also found that the pulmonary vascular resistance was similar to ambient air breathing. In accordance with healthy volunteers and patients with cardiovascular diseases or COPD, exercise performance as assessed by the 6 MWD was reduced at altitude and irrespective of whether NOT or placebo were applied during the nights ( 11 , 24 ).…”
Section: Discussionmentioning
confidence: 63%
“…In our previous short-duration study with normobaric hypoxia, PH patients revealed an even smaller fall in arterial oxygen tension compared to unaffected controls while breathing hypoxia during 15′, related to increased hyperventilation as indicated by the significant decrease in arterial partial pressure of carbon dioxide (PaCO 2 ) ( 8 ). In healthy volunteers, exercise performance is gradually impaired with increasing hypoxia/altitude ( 9 ) and even more in patients with COPD ( 10 , 11 ) and improves with adaptation ( 12 ). Data on PH patients exercising at altitude is completely lacking.…”
Section: Introductionmentioning
confidence: 99%